Direct development of the catfish pectoral fin: An alternative pectoral fin pattern of teleosts. Issue 11 (4th July 2022) - Shkil, Fedor; Kapitanova, Daria; Borisov, Vasily; Veretennikov, Nikolay; Roux, Natacha; Laudet, Vincent
Abstract: Background: The study of the teleosts' pectoral fin development touches on many crucial issues of evolutionary biology, from the formation of local adaptations to the tetrapod limbs' origin. Teleosts' pectoral fin is considered a rather developmentally and anatomically conservative structure. It displays larval and adult stages differing in the skeletal and soft tissues' composition. Larva‐adult transition proceeds under the thyroid hormone (TH) control that defines pectoral fin ontogeny as an indirect development. However, the outstanding diversity of teleosts allows suggesting the existence of lineage specific developmental patterns. Results: We present a description of the North African catfish, Clarias gariepinus, pectoral fin development. It lacks a clear larval stage and directly develops the adult skeleton with the associated musculature and innervation. Interestingly, the development of catfish pectoral fin appears not to be under the TH dependence. Conclusion: This catfish displays a direct pectoral fin developmental trajectory differing from the stereotyped teleost pattern. In the absence of the larval endoskeletal disk and TH control, the catfish's proximal radials arise in a manner somewhat similar to the metapterygial radials in basal actinopterygians and humerus in sarcopterygians. Thus, the catfish fin pattern seems homoplastic, arising by convergence with, or reversion to the ancestral developmental mechanisms. Key Findings: The North African catfish's pectoral fin development differs from the stereotyped teleosts' pattern. It lacks the larval stage and clear thyroid hormones dependence and should be regarded as direct development. In the absence of the endoskeletal disk, the catfish's proximal radials arise in a manner somewhat similar to the metapterygial radials in basal actinopterygians and limb bones in sarcopterygians.